Distorted mirrors Americans and their relations with Russia and China in the twentieth century - Davis, Donald E., 1936- (University of Missouri Press, 2009)
"Drawing on memoirs, archives, and interviews, Davis and Trani trace American prejudice toward Russia and China by focusing on the views of influential writers and politicians over the course of the twentieth century, showing where American images originated and how they evolved"--Provided by publisher.